Orthodontic Treatment for a Patient with Root Resorption of All Four Maxillary Incisors due to Bilaterally Impacted Canines - Makoto Yanoshita; Naoto Hirose; Azusa Onishi; Sayuri Nishiyama; Naoki Kubo; Daiki Kita; Kotaro Tanimoto (Case Reports in Dentistry)
Maxillary canines require the longest period from the generation of the tooth germ to the completion of eruption, and they have more difficulties in eruption than other teeth. The incisor roots are often resorbed due to malpositioned canines. An 11-year-old girl presented with an extremely rare case of root resorption of four maxillary incisors due to bilaterally impacted maxillary canines, which were located excessively mesially. The case was managed through oral surgery and orthodontic treatment over five years. After extracting the maxillary deciduous canines, the maxillary bilateral canines were surgically exposed. The bimaxillary lateral incisors were extracted, and the canines were orthodontically tracted over 8 months. All teeth were then aligned using edgewise brackets. No further root resorption of the central incisors was observed for 5 years after canine traction. This case demonstrates the importance of early detection of abnormally positioned canines.